The Influence of Village Financial System Applications on Fraud Prevention with Competence as Moderator in Village Fund Management - Afriady, Arif (Management Science Research Journal, 2024)
This research is based on the intention to provide a wealth of knowledge regarding village fund management and provide a review of the use of the SISKEUDES application and the role of competence in village fund management. The data has been taken from village officials using questionnaires. The analysis method in this study uses path analysis with the help of SEM PLS tools. The results show that there is a direct influence of the SISKEUDES Application on Fraud Prevention in village fund management in Babakan Cikao Village, Purwakarta. Competence is also able to strengthen the influence of the SISKEUDES application on preventing fraud in village fund management. This shows the importance of increasing the competence of village officials to be able to operate the SIKEUDES application. Competence can be in the form of training, routine assistance or formal education needed by village officials